Implementation And Effect Of Sensor Technology In Building Level Balancer Using Programmable Integrated Circuit Microcontroller - Nik Azran, Ab Hadi (UTeM, 2016)
Recent advances in sensor technology would lead to a new trend of instrumentation system that can be used in the construction industry.In this paper,a level balancer has been developed which is an instrument that can be used in the construction sector for measuring and determining the equality between two pillars height (elevation) and horizontal surfaces.Similarity and equality of the surface and elevation is important in the construction sector to ensure that the structures can be stay strong and avoid the building from collapse.This paper proposed a level balancer with two methods that are using a combination of magneto-resistive sensor and laser and the other one is using barometric sensor based on Programmable Integrated Circuit (PIC) microcontroller.In method 1,the level balancer is built with magneto-resistive sensor for measuring angles, combined with Liquid Crystal Display (LCD) screen for displaying horizontal angle of 180 degrees,and a specially built laser device.This combination of devices can produce a horizontal straight line at angle 180 degrees to ensure that the elevation between two pillars is same.Meanwhile, method 2 consists of a barometric sensor for measuring altitude attained, and LCD screen for displaying altitude value.This project can be implemented as level balancer measuring tool by labor and building developer with accuracy almost 99.9% and the 0.01% error can be neglected.